2016
DOI: 10.1016/j.cardfail.2016.06.161
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Initial Volume Resuscitation for Sepsis in Patients with Congestive Heart Failure: Is it Associated with Higher Mortality

Abstract: The sum of all 12 QRS amplitudes during the acute phase was 5.13 ± 0.96 mV and increased to 8.14 ± 1.68 mV (P = .001) during the recovery phase. Ejection fraction was 31 ± 6% during the acute phase and improved to 52 ± 11% (P = .001) during the recovery phase. There was a downward trend of septal thickness from 0.98 ± 0.15 cm to 0.84 ± 0.07 cm (P = .056) during the recovery, while left ventricular diastolic dimension remained unchanged (P = .77). None of the patients had a significant pericardial effusion. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The 2016 Surviving Sepsis Campaign guideline issued a recommendation for using a minimum of 30 mL/kg (ideal body weight) of intravenous crystalloids in initial fluid resuscitation (2). Previous studies on fluid management in patients with sepsis with HF have mainly focused on this bundle implementation (24)(25)(26). Most sepsis patients require continued fluid administration following initial resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…The 2016 Surviving Sepsis Campaign guideline issued a recommendation for using a minimum of 30 mL/kg (ideal body weight) of intravenous crystalloids in initial fluid resuscitation (2). Previous studies on fluid management in patients with sepsis with HF have mainly focused on this bundle implementation (24)(25)(26). Most sepsis patients require continued fluid administration following initial resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…8 Clinicians are particularly concerned about the potential harms of empirical fluid administration to patients with underlying heart failure with reduced ejection fraction (HFrEF), who may be at higher risk of complications. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 A greater understanding of the epidemiology of preexisting HFrEF prior to sepsis and its association with outcomes is needed to balance the pros and cons of fluid resuscitation for these patients at high risk. To address these knowledge gaps, in a multicenter cohort study, we explored the epidemiology of HFrEF diagnosed prior to hospitalization for sepsis and its risk-adjusted association with guideline-recommended intravenous fluid administration and outcome during emergency care of septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…In a published scientific abstract (full length manuscript not published), Singh et al studied the effect of initial volume resuscitation for sepsis in patients with CHF (left ventricular ejection fraction <40%). 16 Of a total of 505 patients included in the study for sepsis, 151 had low ejection fraction. The authors found higher in-hospital mortality in septic patients with low EF, who received >3 L initial fluids.…”
Section: Discussionmentioning
confidence: 99%